The Impact of the Implementation Three-Step Interview Cooperative Learning Model in Mathematics Learning Toward the Learners’ Activities And Outcomes - Usmadi, Usmadi; Hasanah, Hayatul; Ergusni, Ergusni (Universitas Malikussaleh, Aceh Utara, Indonesia, 2020)
This study is motivated by the issues found in observations at school, where the daily teaching activities carried out by teachers show that; teaching and learning activities are classical, the teacher only stands or sits in front of the class, the direct relationship between the teacher and students is rare, and students tend to behave passively, such as coming, listening, reading and writing. To overcome this issues, the researchers conducted a research by applying a three-step type of cooperative learning model interview in learning mathematics in the class. The purpose of this study is to reveal the activities and learning outcomes of students after applying the three-step interview type cooperative learning model. From the results of the study it was found that the learning activities of students during the application of the three step interview cooperative learning model increased at each meeting. Thus it can be concluded that the mathematics learning outcomes of students with learning by applying a three-step interview type cooperative learning model is better than those who do not apply the techniques.